2012
DOI: 10.1177/0016986212469999
|View full text |Cite
|
Sign up to set email alerts
|

Homeschooling the Gifted

Abstract: Homeschooling has witnessed a dramatic growth over the past decade. Included in this population are gifted and talented students, yet despite this growth there has been no appreciable increase in the research literature. To better understand the gifted homeschooling family, researchers interviewed 13 parents of homeschooled children their parents identified as being gifted. Four major themes emerged from the data: (a) parents know best, (b) isolation, (c) challenges, and (d) family roles. Findings reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
3
13
0
11
Order By: Relevance
“…These findings are also consistent with those of other studies that have shown that older homeschooled children feel isolated (Jackson, 2016;Kunzman, 2009), as in the case of gifted homeschooled children (Jolly, Matthews, & Nester, 2013;Winstanley, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are also consistent with those of other studies that have shown that older homeschooled children feel isolated (Jackson, 2016;Kunzman, 2009), as in the case of gifted homeschooled children (Jolly, Matthews, & Nester, 2013;Winstanley, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In the group that had always homeschooled, 43.4% had a child with SEN. These findings support the contention of prior research that parents of children with SEN may be choosing to homeschool when they believe their child's needs are not being met in the traditional classroom (Arora, 2006;Jolly et al, 2013;Parsons & Lewis, 2010;Reilly et al, 2002). These findings are also consistent with results of prior studies that focused on families homeschooling children with SEN (Arora, 2006;Parsons & Lewis, 2010;Reilly et al, 2002), which found that a high percentage of families homeschooling children with SEN had placed their child(ren) in a public or private school before they made the decision to homeschool.…”
Section: Discussionsupporting
confidence: 83%
“…Three main special education needs populations where homeschooling is being used were identified as high ability and gifted students, students with attention deficit/hyperactivity disorder (AD/HD), and students with Asperger's Syndrome or autism (collectively referred to as Autism Spectrum Disorder or ASD). Jolly, Matthews, and Nester (2013) used a phenomenological approach to gain an understanding of families that are homeschooling gifted children. Only 1 of the 13 families interviewed chose to homeschool their child without first attending public and/or private schools.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Taken collectively, these studies suggest causes for excellence gaps and discrepancies in performance gaps among states, with economically successful states tending to have more programming than less successful states (i.e., the rich get richer while the poor get poorer). But these studies also provide evidence that upper-income families will look to private education or other out-of-school means such as homeschooling when their talented students’ needs are not being met (Jolly, Matthews, & Nester, 2013), and that even under positive economic conditions, programming can concentrate in certain communities. These factors help create a vicious cycle in which excellence gaps continue to widen, leading to an unfortunate side effect of a lack of gifted education policy: When services are not provided, families with the knowledge and resources to identify and take advantage of opportunities will do so, further exacerbating inequality.…”
Section: Previous Policy Researchmentioning
confidence: 99%